Cyber-Physical System (CPS) Application-A REVIEW - Syarfa Najihah Raisin; Fatinah Mohd Rahalim; Farah Aina Mohd Jamal; Nur Arina Hazwani Samsun Zaini; Bushra Naeem; Juliza Jamaludin (Institut Teknologi Nasional Bandung, 2024)
Volume :1 No : 2